VD_FINDINFO AI 9/08 - 2/2010 vom 4. Januar 2010 - VD Tribunal cantonal (2010)
AIASSURANCE, ÉVALUATION DE L'INVALIDITÉ, FORCE PROBANTE, COORDINATIONASSURANCE, STATISTIQUE | 28 al. 1 LAI, 16 LPGA, 7 LPGA, 8 LPGA